PMSM model with inter-turn fault - C. Bouchareb; MS. Nait-Said (2015 4th International Conference on Electrical Engineering (ICEE), 2015)
Stator winding faults are one of most frequent PMSM motor damages resulting from the degradation of the inter-turn, inter-phase and main isolation of the motor winding. So this paper presents a dynamic model for PMSM with inter-turn fault. The faulty model is used for studying the machine behavior and extracting the fault signatures.